Gender inequality in hospitality industry and impact of gender-focused policies in lessening gender inequality - Caceres, Isles Rouie C.; Calanoy, Daenielle May S.; Regalado, Frances Elaine G.; Sayco, Lynnette M. (2019.)
The study aims to determine if gender iequality exists in the hospiitality industry in Iloilo City. The researchers use a correlational design and explanatory theory in which two variables are being examined through statistical analysis. Survey forms are used to collect data to four hotels in Iloilo City with 60 respondents. The extent of gender inequality as perceived by the management level is high, while there is low gender inequality as perceived by the non-management level in the hospitality industry. In accordance to the Gender Audit Handbook, the mean score of 3.03 in the overall level of gender-focused policies and practices implementation, shows that gender policies and practices are considerably integrated in a moderate extent thus there is quite low gender inequality. The extent of level of implementation of gender-focused policies and practices using Gender Audit Handbook is high in the hospitality industry. Thus, the results show that there is high level of gender-focused policies and practices implementation, thus gender inequality is low in hospitality industry in Iloilo City.
Undergraduate Research Project (B.S. Management). -- [Iloilo City] : University of the Philippines Visayas - College of Management, June 2019.